Are Connected and Automated Vehicles the Silver Bullet for Future Transportation Challenges? Benefits and Weaknesses on Safety, Consumption, and Traffic Congestion - Gruyer, Dominique; Orfila, Olivier; Glaser, Sébastien; Hedhli, Abdelmename; Hautière, Nicolas; Rakotonirainy, Andry (Frontiers in Sustainable Cities, 2021)
With the growing development of Cooperative, Connected, and Automated Mobility (CCAM), questions arise about the real impact of this innovative mobility on our daily life. CCAM originally promises to improve road safety. It is now a holistic solution to future mobility: the CCAM is to optimize traffic, which can translate into strategies for reducing energy consumption or polluting emissions, without compromising road safety. The capability of CCAM is dependent on the reliability and robustness of its components, as it will take life-impacting decision. It is therefore necessary to be able to guarantee a high level quality of sensors, communication, software and hardware architecture. In this mobility ecosystem, the infrastructure and the data that it will be able to produce, is at the heart of current research issues. This paper addresses this very cross-cutting question: Are the Connected and automated Vehicles (CAVs) the silver bullet solution to answer the issues of the current mobility systems? This question is discussed by investigating the technologies used, the digital infrastructures, its robustness to cyber-attack, and their relations with the claimed benefits on safety, energy and pollution management, and traffic optimization, as well as the deployment strategy and the link with the new generation of road infrastructures.